Perception of Marketing Professionals towards Digital Marketing: Application of TAM Model - Dr. Bharti Motwani, Dr. Sharda Haryani (International Journal of Advanced Science and Technology, 2020)
Digital marketing is a latest marketing model that involves marketing activities with respect to information technology to improve customer satisfaction by fulfilling their requirements. Online advertising is effective for measuring ROI on advertisement and effective for brand building and increasing number of customers for companies to achieve success. The purpose of this research paper is to determine the true picture of digital marketing with respect to business process outcomes. Four factors related to TAM model of digital marketing namely Perceived Usefulness, Perceived Attitude, Perceived Ease of Use and Perceived Security are considered as independent variables, while satisfaction related to business process outcomes is considered as dependent variable. Non probability judgmental sampling method was used for the collection of primary data from 220 marketing professionals who have adopted digital marketing in their business. Regression analysis using R software was done to study the results and found that all the four factors are significant for achieving effective results in an organization.